2019
DOI: 10.1248/bpb.b18-00974
|View full text |Cite
|
Sign up to set email alerts
|

Fragility Fractures in Older People in Japan Based on the National Health Insurance Claims Database

Abstract: Fragility fractures associated with age-related bone loss are of urgent concern worldwide because they reduce QOL and pose financial burdens for health care services. Currently, national data in Japan are limited. This study provides quantitative data for older patients throughout Japan who, although otherwise relatively healthy, sustained fragility fractures and were hospitalized for them. The National Database of Health Insurance Claims and Specific Health Checkups of Japan was accessed to target patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…The results of the present study showed that the risk of fragility fracture associated with the use of hypnotics and sedatives and anxiolytics was statistically nonsignificant for the analyses with a 3-d window, but marginally significant in analyses with longer windows. Results of previous studies are controversial; the association was nonsignificant in the metaanalysis by Takkouche et al 3) and in a case-crossover study by Leach et al, 4) and the RR was 1.5 14) and 1.2 15) in two other meta-analyses.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…The results of the present study showed that the risk of fragility fracture associated with the use of hypnotics and sedatives and anxiolytics was statistically nonsignificant for the analyses with a 3-d window, but marginally significant in analyses with longer windows. Results of previous studies are controversial; the association was nonsignificant in the metaanalysis by Takkouche et al 3) and in a case-crossover study by Leach et al, 4) and the RR was 1.5 14) and 1.2 15) in two other meta-analyses.…”
Section: Discussionmentioning
confidence: 84%
“…a The detailed flowchart to identify patients who incurred fragility fractures is illustrated elsewhere. 16) antiepileptic agents in the case window (i.e., immediately before incurring the fracture) but did not use them in the control windows was certainly higher than the opposite pattern, suggesting that the use of antiepileptic agents, not the occurrence of seizures, caused fragility fractures. This is because an antiepileptic agent would have been used after a fracture if a seizure caused the fracture.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations